Glazed PVT Collector with Polysiloxane Encapsulation of PV Cells: Performance and Economic Analysis - Tomas Matuska; Borivoj Sourek; Vladimir Jirka; Nikola Pokorny (International Journal of Photoenergy)
Development of a new concept of glazed PVT collector based on temperature resistant polysiloxane encapsulation material is presented together with the results from experimental testing and modelling. Performance and economic analysis in 4 different European climates has been done to derive the competitive price of the PVT collector concepts with main focus on the glazed PVT collector under development. Results have shown that specific market price 400 to 500 EUR/m2 for the glazed PVT collector should not be exceeded in order to become competitive with conventional combination of photothermal and photovoltaic collectors.